Noninvasive detection of macrophages in atherosclerotic lesions by computed tomography enhanced with PEGylated gold nanoparticles - Qin J (Dove Medical Press, 2014)
Jinbao Qin,1,* Chen Peng,2,* Binghui Zhao,2,* Kaichuang Ye,1 Fukang Yuan,1 Zhiyou Peng,1 Xinrui Yang,1 Lijia Huang,1 Mier Jiang,1 Qinghua Zhao,3 Guangyu Tang,2 Xinwu Lu1,4 1Department of Vascular Surgery, Shanghai Ninth People’s Hospital Affiliated to Shanghai JiaoTong University, School of Medicine; 2Department of Radiology, Shanghai Tenth People’s Hospital Affiliated to Tongji University, School of Medicine; 3Department of Orthopaedics, Shanghai First People’s Hospital, School of Medicine, Shanghai Jiao Tong University; 4Vascular Center of Shanghai JiaoTong University, Shanghai, People’s Republic of China *These authors contributed equally to this work Abstract: Macrophages are becoming increasingly significant in the progression of atherosclerosis (AS). Molecular imaging of macrophages may improve the detection and characterization of AS. In this study, dendrimer-entrapped gold nanoparticles (Au DENPs) with polyethylene glycol (PEG) and fluorescein isothiocyanate (FI) coatings were designed, tested, and applied as contrast agents for the enhanced computed tomography (CT) imaging of macrophages in atherosclerotic lesions. Cell counting kit-8 assay, fluorescence microscopy, silver staining, and transmission electron microscopy revealed that the FI-functionalized Au DENPs are noncytotoxic at high concentrations (3.0 µM) and can be efficiently taken up by murine macrophages in vitro. These nanoparticles were administered to apolipoprotein E knockout mice as AS models, which demonstrated that the macrophage burden in atherosclerotic areas can be tracked noninvasively and dynamically three-dimensionally in live animals using micro-CT. Our findings suggest that the designed PEGylated gold nanoparticles are promising biocompatible nanoprobes for the CT imaging of macrophages in atherosclerotic lesions and will provide new insights into the pathophysiology of AS and other concerned inflammatory diseases. Keywords: atherosclerosis, CT, in vivo imaging